Antioxidant and antibacterial activity of mangrove Brugueira gymnorrhiza stem extracts against pathogenic bacteria Vibrio cholerae - Angga Crystal Loasana Yami; Irmanida Batubara; Kholis Abdurachim Audah (Indonesian Society for Biochemistry and Molecular Biology, 2020)
Background : The treatment of some diseases caused by free radicals and pathogenic bacteria usually by using antioxidants and antibiotics. Due to excessive use of antibiotics and other environmental cues, some bacteria are now resistant to certain antibiotics or even to multiple antibiotics. Some Vibrio cholerae bacterial strains are multiresistant to many antibiotics. Objective : The antioxidant and antibacterial activities of Brugueira gymnorrhiza stem extracts against pathogenic bacteria V. cholerae. Method : The B. gymnorrhiza stem was extracted by gradient maceration method. The DPPH method was used to determine the antioxidant activity and the disc diffusion method was used to determine the antibacterial activities. The column chromatography method was used to fractionate the selective extract with the best activity. The LC-MS/MS method was used to identify the compound obtained from the fraction with the best antioxidant and antibacterial activity. Result : Ethyl acetate extract of B. gymnorrhiza stem had the best antibacterial activity with MIC and MBC values of 62.50 mg/L. Ethyl acetate extract also showed the best value of antioxidant activity as indicated by an IC50 value of 255.03 mg/L. The results of fractions test showed that fraction 3 had the best antibacterial and the best antioxidant activities with both the MIC and MBC values of 7.90 mg/L and IC50 value of 348.91 mg/L, respectively. Conclusion : Ethyl acetate extract of B. gymnorrhiza stem has good potential as antioxidant and antibacterial. The compound which is thought as antioxidant and antibacterial from Ethyl acetate extract is 2-Ethyl-4-methyl-1H-imidazole.